Calcium Alginate-Neusilin US2 Nanocomposite Microbeads for Oral Sustained Drug Delivery of Poor Water Soluble Drug Aceclofenac Sodium. (23rd February 2015) - Mallappa, Manjanna Kolammanahalli; Kesarla, Rajesh; Banakar, Shivakumar
Abstract : The aim of the present study was to formulate and investigate the calcium alginate- (CA-) Neusilin US2 nanocomposite microbeads containing preconcentrate of aceclofenac sodium (ACF-Na) liquid microemulsion (L-ME) for enhancement of oral bioavailability. The preconcentrate L-ME is prepared by using Labrafac PG, Labrasol, and Span 80 as oil, surfactant, and cosurfactant, respectively. The solid CA nanocomposite microbeads of L-ME prepared by microemulsification internal gelation technique using sodium alginate (SA) gelling agent, Neusilin US2 as adsorbent, and calcium chloride as crosslinking agent. L-ME has good thermodynamic stability; globule size was found to be 32.4 nm with polydispersity index 0.219 and −6.32 mV zeta potential. No significant interactions of excipients, drug in the formulations observed by FT-IR, DSC and XPRD. The concentration of SA and Neusilin US2 influences the flow properties, mean particle size, mechanical strength, drug entrapment efficiency, and percentage of drug release. All the formulations show minimum drug release in simulated gastric fluid (SGF) pH 1.2 for initial 2 h, maximum drug release in pH 6.8 phosphate buffer solution (PBS) at 6 h, followed by sustaining in simulated intestinal fluid (SIF) of pH 7.4 up to 12 h. The interaction of SA with Neusilin US2 creates a thick thixotropic gel network structure which acts as barrier to control the release of drug in the alkaline pH environment. Neusilin US2 is a novel filler used to convert L-ME into solid nanocomposite microbeads to enhance dissolution rate of poor water soluble drugs sustaining the drug release for prolonged period of time.